Efeitos do laser de baixa intensidade sobre o estresse oxidativo em ratos com diabetes mellitus tipo 2 - Tonetto, Larissa da Silva (2021)
Type 2 DM is the most prevalent and is characterized by defects in secretion and peripheral insulin resistance, which determine oxidative stress (OS). Low level laser therapy (LLLT) is a non-pharmacological tool that has been used for the treatment of DM, by reducing OS and inflammatory activity and increasing antioxidant activity. Thus, the aim of the present study was to evaluate the effects of LLLT on OS in organs, skeletal musculature and serum of rats with DM. Thirty-one male Wistar rats were used, divided into two groups, with DM 2 induction and without DM 2 induction, considering diabetic animals with blood glucose equal to or greater than 200 mg/dL, then the rats were allocated into 4 subgroups: Group 1 - animals without DM 2 SHAM (C-SHAM), Group 2 - animals with DM 2 SHAM (C-DM), Group 3- animals without DM 2 with 21 J/cm2 laser (L-SHAM), Group 4- animals with DM 2 with 21 J/cm2 laser (L-DM). After DM 2 induction or not, the animals received LLLT 5 days/week for 6 weeks. The dose was irradiated at two points in the right gastrocnemius muscle. The laser used was a continuous wave diode InGaAlP type with an output power of 20 mW and a wavelength of 660 nm. The stitch size was 0.035 cm2, dose of 21 J/ cm2, time of 36 seconds in each stitch and continuous frequency. Twenty-four hours after the last day of intervention, the animals were anesthetized and euthanized. Heart, diaphragm, liver, right gastrocnemius, plasma, lungs, kidneys and soleus were collected, weighed and stored for further analysis. LLLT reduced plasma levels of TBARS in animals with DM 2. In the heart, diaphragm and gastrocnemius, LLLT increased NPSH levels in the DM 2 group. In the heart, diaphragm and plasma, the L-DM group increased SOD when compared to the C-DM group. The L-SHAM group increased SOD in the heart, diaphragm, gastrocnemius and kidneys when compared to the C-SHAM group. It is concluded that the 21 J/cm2 LLLT protocol, lasting 6 weeks, decreased the oxidant activity and increased the antioxidant and in rats with DM 2.